La vulnerabilidad victimal de los ancianos y su protección en el código penal: valoración y perspectivas de futuro = Victim vulnerability of the elderly and its protection in the penal code : assessment and future perspectives - Sánchez-Moraleda Vilches, Natalia (Revista de victimología, 2024)
This paper provides a critical examination of the criminal regulation providing enhanced protection of the elderly who are particularly vulnerable or in a state of defenselessness. To this end, it begins by exposing the two models of protection regarding victim vulnerability: one based on the vulnerability of the group the victim belongs to and, in contrast, one that adopts an individualistic approach. Next, we turn to some of the problematic aspects of the aggravated offenses providing increased protection to particularly vulnerable victims. Of particular interest are the concepts of "vulnerability" and "particular vulnerability", the deficient legislative technique used, and the foreseeable consequences. Then (old) age as a category of vulnerability is specifically examined, trying to establish its content and distinguish it from other materially analogous categories, disability and illness. Such examination is completed with a study of the jurisprudential trends, evidencing manifestly contradictory positions in the interpretation of the circumstance. Finally, we conclude with an assessment of the suitability of this kind of vulnerability regulations to prevent and avoid victimization of the elderly, and suggest possibilities for reform to improve the treatment of this criminological reality within criminal law.